Strategic Business Management in India: Driving Growth, Innovation, and Leadership in a Complex Economic Context - Fadnis, Bhushan (Journal of Global Economy, Business and Finance, 2025)
India's business landscape is rapidly evolving, driven by economic growth, technological advancements, and the globalization of markets. This paper examines the critical aspects of strategic business management in India, focusing on how organizations can effectively navigate the complexities of growth, innovation, and leadership in a dynamic economic environment. Key areas of discussion include the importance of strategic planning, fostering innovation, leadership development, and maintaining a competitive advantage. The paper also highlights challenges faced by Indian businesses, such as navigating regulatory environments, managing organizational change, and addressing the talent gap. By exploring these elements, the paper provides insights into how Indian businesses can enhance their management practices to achieve sustainable success in a competitive global market.